Biodegradation of Low-Density Polyethylene (LDPE) Bags by Fungi Isolated from Waste Disposal Soil - null Saira; null Abdullah; Lalina Maroof; Madiha Iqbal; Saira Farman; null Lubna; Shah Faisal (Applied and Environmental Soil Science)
Plastics are available in different shapes nowadays in order to enhance the living standard. But unfortunately, most of these plastics are synthetic in nature that is why they show resistance to physical and chemical degradation processes and enhance environmental hazards. The aim of the present research study was to isolate and identify beneficial fungal species from soil that have the capability to degrade plastic. Soil samples from a waste disposal site at Peshawar district were diluted and inoculated on sabouraud dextrose agar (SDA) and potato dextrose agar (PDA) for fungus isolation. After isolation, the identifications of fungal species were done using standard identification techniques such as colony morphology and microscopic examination. The isolated fungal species that were identified were Aspergillus Niger, Aspergillus flavus, Penicillium, white rot, and brown rot fungi. After isolation, a degradation experiment was conducted to evaluate the capability of fungal isolates towards degradation of plastic. For this purpose, a 2 cm2 plastic piece was treated with fungal isolates for one month in a liquid culture system. The weight loss percentage was estimated at 22.9%, 16.1%, 18.4%, and 22.7% by Aspergillus Niger, Aspergillus flavus, brown rot, and white rot, respectively, which was confirmed by the Fourier transform analysis. The obtained FTIR peaks revealed the C–H bond deformation in alkenes, ketones, and esters. It has been concluded from the study that fungal species play a significant role in the degradation of synthetic plastic which can be used in bioreactors in future studies for the degradation of complex plastic materials.